Wood fiber and green manure as soil improvers in vegetable production - Keskinen, Riikka; Salo, Tapio; Hyvönen, Juha; Rasa, Kimmo; Suojala-Ahlfors, Terhi (Taylor & Francis, 2026)
Introducing sustainable management practices to vegetable farming is necessary for maintaining and enhancing the quality of soil under intensive cultivation. Especially measures to increase organic matter are favorable, but their integration requires research. Clean organic inputs in the form of fiber sludge from the pulp industry or green manure grown on site are promising alternatives for improving vegetable-growing soils. These inputs may, however, alter the nitrogen (N) dynamics of the system and challenge fertilization optimization. In this study, the effects of (1) fiber sludge, (2) composted fiber sludge with broiler manure, and (3) green manure on crop growth, N uptake and soil total carbon (C) and available N contents and water retention were evaluated in a three-year field experiment to assess possibilities of integrating soil-improving measures in high-value cropping. The study involved increasing N fertilizer rates in open field vegetable production. Onions (Allium cepa) grown in the first year following the treatments reflected increased N availability derived from the residual N of the fiber sludge-broiler manure and green manure treatments, but the effect was not consistent over time and between N rates. Minor accumulation of nitrate–N in the subsoil indicated risk of N leaching following green manuring. No soil improving treatment-induced effects were discernible in the soil or crop N in white cabbage (Brassica oleracea convar. Capitata var. Alba) grown on the second vegetable season. Neither soil water retention characteristics nor soil C stocks were affected by the one-time soil improving. For measurable effects, repeated treatments would be needed.
Keywords: cabbages; carbon; nitrogen availability; onion; plant available water